Penerapan Model Pembelajaran Environmental Learning Untuk Meningkatkan Minat Dan Hasil Belajar Ips Mengenai Pengaruh Kenampakan Alam Terhadap Aktivitas Manusia Pada Siswa Kelas V SD Negeri 2 Langon Tahunan Jepara - Sudar, Sudar (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
IPS is one of the areas of study at the elementary school level that studies social problems in society. Due to low student interests and learning outcomes, the researchers carried out learning improvements through Classroom Action Research with two learning cycles. The study aims to find out whether the use of Enviromental Learning learning models can enhance students' interest and learning outcomes in the subject matter IPS Nature Effects on Human Activity. The study was conducted with 39 students in the V class. The results of the study in the pre-cycle were only 15 students who obtained a score ≥ KKM or 38% of the score, with an average score of 2.58. In the 1st cycle there was an increase to 29 students or 74% of the number of students, with a mean score of 3.00, and the second cycle experienced another improvement with a grade of 95%, only 2 students who have not reached the KKM score with a average rating of 3.44. It can then be concluded that the use of Enviromental Learning learning model can increase the interest and learning outcomes of students in IPS subjects on the Impact of Natural Surveillance on Human Activity in Class V of SDN 2 Langon Tahunan Jepara.